Aggressive Behavior and the Role of Antennal Sensillae in the Termite Reticulitermes chinensis (Isoptera: Rhinotermitidae) - Huang, Qiuying (Sociobiology, 2014)
This study examined aggressive behavior between the colonies in the termite Reticulitermes chinensis from China. Strong aggression was observed among workers and soldiers. Intercolonial aggression was strong during the first 0.5 h and then reduced gradually in all the treatments. After cutting the five terminal antennal segments of workers and soldiers, there was still strong intercolonial aggression among workers and soldiers. However, after removal of the ten terminal antennal segments of workers and soldiers, almost no intercolonial aggression happened among workers and soldiers. SEM results of antennae indicated that antennal sensillae mainly occurred on the ten terminal segments including four types of trichode sensilla, both in workers and soldiers of this species. Few antennal sensilla occurred on the basal segments except for a few sensilla chaetica and basiconic capitate peg sensilla. The above findings suggest that antennal sensillae may play a role in nestmate recognition in R. chinensis.